Higher education in the subjects of the Russian Federation: formation of a new network structure of educational organizations - Danilchenko S. L. (Interactive science, 2022)
most of the issues related to the achievements of science and the improvement of the higher education system are closely related to the development of human capital and the strengthening of human resources. Higher education plays a major role in the formation of a person, the development of personality, the acquisition of knowledge, skills, skills and competencies. The professional capabilities of teachers in universities and the availability of high-quality education depend on knowledge and skills, that is, on the level of human capital development. It is on a sufficient number of highly qualified teachers that the training of specialists for the real sector of the economy, the social sphere, the development of the scientific and industrial potential of our country and its leading positions depend
Keywords: обеспечение подготовки высококвалифицированных кадров; территориально-пространственное размещение сети организаций высшего образования; доступ к высшему образованию; новая структура сети образовательных организаций; модели целевого обучения; особенности реализации образовательных программ в сетевой форме; система социальных лифтов для молодых людей; ensuring the training of highly qualified personnel; the territorial and spatial location of the network of higher education organizations; access to higher education; the new structure of the network of educational organizations; models of targeted training; features of the implementation of educational programs in the network form; the system of social elevators for young people